1968
DOI: 10.1039/j19680002535
|View full text |Cite
|
Sign up to set email alerts
|

Reactions between organoaluminium compounds and N-substituted acid amides

Abstract: Reactions between R13AI and R2NH*C0.R3 (R1 = Me or Et; R3 = Me or Ph) leading to materials ( R1,AI*NR2*CO*R3), are described. 1.r.. mass, and lH n.m.r. spectroscopic details of the products are given. Cyclic 8-membered ring structures (n = 2) are proposed for these compounds in the solution phase. Cryoscopic studies support dimeric structuresfor the compounds (Me,AI.NPh*CO*Me), and (Me,AI.NBut.CO.Me), in benzene, although an X-ray crystallographic study of the former, which can also be prepared from Me3Al and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…[37,51] Examples are known with both O and N atoms bridging in hydroxypyridine ligands (in an isolobal disposition to carboxylatebridged ligands) [25] or with an amidate group [52][53][54][55] between two aluminium atoms.…”
Section: Resultsmentioning
confidence: 99%
“…[37,51] Examples are known with both O and N atoms bridging in hydroxypyridine ligands (in an isolobal disposition to carboxylatebridged ligands) [25] or with an amidate group [52][53][54][55] between two aluminium atoms.…”
Section: Resultsmentioning
confidence: 99%
“…First results on reactions between organoaluminum compounds and N-substituted acid amides were reported in 1966 by Tani et al [1]. In 1968, Wade et al [2], Lappert et al [3] and Tani et al [4] published [Me 2 Al(RNC(O)R 0 )] 2 compounds as the dimeric molecules composed of a centrosymmetrical eight-membered ring with aluminum atoms bridged by OCN groups. The alkylaluminum amidates have been of considerable interest for their activity in acetaldehyde polymerization [4] and transamidation of secondary carboxamides [5].…”
Section: Introductionmentioning
confidence: 94%
“…Although oxamidate ligands deserve a particular attention in the supramolecular chemistry [10], group 13 oxamidates are rather poorly described. It was demonstrated in 1975, that trialkyl derivatives of gallium and indium reacted with N,N 0 -dimethyloxamide to yield products of the general formula (R 2 M) 2 (CONMe) 2 [11]. On the basis of the NMR spectroscopy and X-ray diffraction studies, Fischer and Stezowski [12] found that the gallium compounds can exist in the form of two configurational isomers, A and B (Scheme 1).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Amidate ligand complexes have been shown to support a variety of transition [19][20][21][22][23] and rare-earth metals [24][25][26][27][28] that has resulted in a family of useful reagents for metalmediated transformations. The synthesis of Al-amidate complexes was originally reported by Lappert and Horder [29] and Wade et al, [30] and was expanded on by the Lin group to include various substituents in the amidate ligand. [31,32] The MacBeth group has more recently reported the preparation of a tris(amidate)aluminium complex implementing a tripodal ligand.…”
Section: Introductionmentioning
confidence: 99%